Play and Mathematics - Francis, Krista (Journal of the Canadian Association for Curriculum Studies, 2019)
In this paper, I argue that a lack of play and joy in classrooms could be due to our North American standardized education system, which emphasizes achievement outcomes. I argue that this system does not benefit the majority of students, nor the field of mathematics. Many students are negatively affected—both emotionally and academically—by a focus on results. Rather than outcome-driven pedagogy, a focus on learning to enjoy doing mathematics might change the conversation. A kinder, process-driven approach through mathematical play may spark enjoyable teaching and learning. Play (Gadamer, 1960/1989; Huizinga, 1944/1949) has the potential to absorb learners as they seek answers to fun yet challenging mathematics problems. The experience of flow is similar to that of play (Csikszentmihalyi, 2000); when playing, learners get a chance to practice and elaborate on their existing skills in manners that suspend notions of time. When the play releases them from its grasp, learners experience the joy from solving problems. Dewey (1916) considered play to be purposeful activity that sponsors a child’s growth. Teachers could capitalize on this for growth in learning. Learning to bring mathematical play into the classroom requires intention, an inviting attitude, knowledge of the types of problems that invoke play, and knowledge of how to connect playful problems to mathematical concepts and curriculum. Such engaging experiences with mathematics could sponsor joyful engagement in mathematics and an intrinsic desire to learn more.